Productivity and relationships of the index of site with fisiographics, edafoclimatic and foliar variable for Tectona grandis L.F., Bombacopsis quinatum (Jacq.) Dugand and Gmelina arborea Roxb. in Costa Rica - Vallejos Barra, O.S. (1996)
34 fig. 50 tab. Bib. p. 126-131. Sum. (En, Es)